Exocrine Pancreatic Insufficiency and Malnutrition in Chronic Pancreatitis: Identification, Treatment, and Consequences. Issue 8 (September 2018) - Min, May; Patel, Boskey; Han, Samuel; Bocelli, Lisa; Kheder, Joan; Vaze, Aditya; Wassef, Wahid
Abstract : Objectives: The purpose of this study was to examine the impact of exocrine pancreatic insufficiency (EPI) on chronic pancreatitis (CP) patients and to identify challenges with its diagnosis and treatment. Methods: Ninety-one patients with CP diagnosed with endoscopic ultrasound were identified and assessed for symptoms of EPI, fat-soluble vitamin levels, dual-energy x-ray absorptiometry scan T-scores, and treatment with pancreatic enzyme replacement therapy. All patients were also screened with the Malnutrition Universal Screening Test. Results: Exocrine pancreatic insufficiency was diagnosed in 84.6% (77/91) of patients based on symptoms of bloating, steatorrhea, or weight loss. Of these patients, 35.2% (19/54) had vitamin A deficiency, 62.5% (55/88) had vitamin D deficiency, and 17.7% (9/51) had vitamin E deficiency. Either osteopenia or osteoporosis was found in 68.9% (31/45). A medium or higher risk for malnutrition based on Malnutrition Universal Screening Test score of 1 or higher was found in 31.5% (28/89). Malnutrition Universal Screening Test score of 1 or higher was associated with an increased risk for osteopenia and osteoporosis on Fisher's exact test ( P = 0.0037). Conclusions: There is a high prevalence of fat-soluble vitamin deficiencies, osteopathy, and malnutrition in CP patients, which is underestimated due to a lack of effective diagnosis and suboptimal therapies for EPI.